Simple Fecal Flotation Is a Superior Alternative to Guadruple Kato Katz Smear Examination for the Detection of Hookworm Eggs in Human Stool - Inpankaew, Tawin; Schär, Fabian; Khieu, Virak; Muth, Sinuon; Dalsgaard, Anders; Marti, Hanspeter; Traub, Rebecca J.; Odermatt, Peter (PLOS Neglected Tropical Diseases, 2014)
Author Summary Hookworm infection is widespread in resource-poor countries worldwide. Detection of hookworm eggs in human feces can be done by the Kato Katz technique (KK), sodium nitrate flotation technique (SNF) or PCR. This study was conducted to evaluate and compare the diagnostic parameters of the KK and simple SNF in terms of detection and quantification of hookworm eggs, with PCR as an additional reference test in stool, collected as part of a baseline cross-sectional study in Cambodia. PCR demonstrated the highest sensitivity for hookworm detection. By microscopy, SNF of a single stool sample proved superior for the detection of hookworm eggs in feces than quadruple Kato Katz smears. Hookworm egg counts were higher by SNF than those obtained using Kato Katz. Thus, the SNF proved superior to the quadruple Kato-Katz smears for the detection of low egg burdens and for the quantification of egg intensities. We propose the simple SNF is a superior alternative to the Kato-Katz for detection and quantification of hookworm infection in resource poor counties. The test is cost-effective and easily accessible.